2012
DOI: 10.1159/000332326
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Dependent Akt1 Activation Regulates PGC-1 Expression and Fatty Acid Oxidation

Abstract: Background: Poly-N-acetyl glucosamine nanofibers derived from a marine diatom have been used to increase cutaneous wound healing. These nanofibers exert their activity by specifically activating integrins, which makes them a useful tool for dissecting integrin-mediated pathways. We have shown that short-fiber poly-N-acetyl glucosamine nanofiber (sNAG) treatment of endothelial cells results in increased cell motility and metabolic rate in the absence of increased cell proliferation. Results: Using a Seahorse Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 99 publications
1
10
0
Order By: Relevance
“…1(B)). Since the gene expression of PGC-1α was induced by activated AKT signaling in human umbilical vein endothelial cells, 26) these results suggest that PGC-1α might be related to the expression level of GLUT1 in the skeletal muscle of newly hatched chicks. Although the newly hatched chicks are adapted to metabolize lipid and protein substrate from egg yolk and albumen, the first feeding leads them to drastic alterations in glucose metabolism.…”
mentioning
confidence: 76%
“…1(B)). Since the gene expression of PGC-1α was induced by activated AKT signaling in human umbilical vein endothelial cells, 26) these results suggest that PGC-1α might be related to the expression level of GLUT1 in the skeletal muscle of newly hatched chicks. Although the newly hatched chicks are adapted to metabolize lipid and protein substrate from egg yolk and albumen, the first feeding leads them to drastic alterations in glucose metabolism.…”
mentioning
confidence: 76%
“…Short poly-N-acetyl glucosamine (sNAG) nanofibers have been found to activate the integrin receptor on the surface of platelets, promote the formation of fibrous protein complexes and cell proliferation and migration, and stimulate the release of a variety of growth factors (6,7). The activated integrin receptor was also found to increase the expression of vascular endothelial growth factor (VEGF) and accelerate the formation of new blood vessels through a transcriptional factor-dependent signaling pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies using these nanofibers in vitro and in vivo , have shown that these fibers directly bind to and stimulate integrin mediated outside/in signal transduction that is, at least in part, dependent on Akt1 activation [ 15 , 16 ]. This activity appears to be due to their unique three dimensional beta quaternary structure.…”
Section: Introductionmentioning
confidence: 99%
“…This activity appears to be due to their unique three dimensional beta quaternary structure. We have shown that nanofiber stimulation results in increased metabolism [ 17 ], increased endothelial cell motility and angiogenesis [ 16 ] and importantly to enhanced innate immune responses leading to antibacterial activity [ 8 ]. These findings indicate that pGlcNAc nanofibers may provide a combinatorial therapy using a single FDA approved agent.…”
Section: Introductionmentioning
confidence: 99%